Parmotrema Perlatum: A Lichen& Indian Spice –Evaluation Of Phytoconstituents & Hepatoprotective Potential Of Its Aqueous Extract - Babu, C. Naresh; Fardeen, S. Baba; Nitish, G. Balaji; Javeed, P. Shaik; Peera, S. Mahaboob; Sai, M. Kiran; Jyothi, M. Vijaya (Journal of Neonatal Surgery, 2025)
Background: Common colloquial names for the lichen Parmotrema perlatum, which belongs to the Parmeliaceae family, include Kalpasi, Raathi puvvu, Kallu hoovu, and Chadila. It usually grows on rocks in temperate regions and flourishes in humid oceanic and suboceanic habitats. Bioactive components of Parmotrema perlatum include phenolic compounds, alkaloids, flavonoids, steroids, and derivatives of usnic acid. It has long been used as a spice in Indian cooking and in traditional medicine to treat ailments like dermatitis, asthma, respiratory, and inflammatory problems. These substances raise the possibility of pharmacological actions, which calls for more research. Methods: To determine the active ingredients in an aqueous extract of Parmotrema perlatum, chemical testing, phytochemical screening, and Gas Chromatography-Mass Spectrometry (GC-MS) analysis were performed. Furthermore, ethanol was utilized to cause liver damage in a Wistar albino rat model in order to assess in vivo hepatoprotective efficacy. The protective effect of the extract was evaluated by looking at the histological alterations in liver tissue. The typical reference medication for comparison was silymarin. Results: Alkaloids, flavonoids, steroids, and cardiac glycosides were detected by phytochemical examination. Compounds with a variety of pharmacological properties, including 5,7-dihydroxy-4-methyl coumarin, Platambin 1,6-dione, Sigmasten 3,5-diene, 1,2-longidione, and Gamolenic acid, were discovered by GC-MS analysis. In ethanol-induced hepatotoxic Wistar rats, the aqueous extract of Parmotrema perlatum showed notable hepatoprotective action at a dose of 200 mg/kg. Conclusion: Parmotrema perlatum aqueous extract exhibits significant hepatoprotective potential, most likely as a result of the presence of many bioactive phytochemicals that were discovered by GC-MS analysis. These results underline the lichen's potential for additional pharmacological research while confirming its traditional use in the treatment of liver-related conditions